2005
DOI: 10.1038/sj.bjc.6602310
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and complement-dependent cytotoxicity of Ep-CAM-specific monoclonal antibody MT201 against breast cancer cell lines

Abstract: MT201 is a fully human monoclonal IgG1 antibody with moderate affinity for epithelial cell adhesion molecule (Ep-CAM) being clinically developed for the treatment of carcinomas. Like many other clinically validated IgG1 monoclonal antibodies, MT201 primarily acts by antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). Here, we analysed ADCC and CDC induced by MT201 and, as reference, trastuzumab against a panel of nine human breast cancer cell lines expressing distinct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
94
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 46 publications
13
94
0
1
Order By: Relevance
“…In this case, the selected cell lines were MCF7 and MDA-MB231, both derived from a pleural effusion of a human breast adenocarcinoma; MCF7 is documented to have high expression levels of EpCAM. On the contrary, MDA-MB231 shows a very low expression (Prang, Preithner et al, 2005). To ensure this point, EpCAM expression was analyzed by Western blot using an anti-EpCAM antibody ( Figure 2) in both cell lines, confirming the previously published results.…”
Section: Epcam Immunoliposomessupporting
confidence: 84%
“…In this case, the selected cell lines were MCF7 and MDA-MB231, both derived from a pleural effusion of a human breast adenocarcinoma; MCF7 is documented to have high expression levels of EpCAM. On the contrary, MDA-MB231 shows a very low expression (Prang, Preithner et al, 2005). To ensure this point, EpCAM expression was analyzed by Western blot using an anti-EpCAM antibody ( Figure 2) in both cell lines, confirming the previously published results.…”
Section: Epcam Immunoliposomessupporting
confidence: 84%
“…The therapeutic effect of this antibody administered alone or in combination with chemotherapy or GM-CSF (Mellstedt et al, 2000) was not conclusive, but it showed a very benign safety profile (Fields et al, 2002;Punt et al, 2002;Hartung et al, 2005). To reduce immunogenicity and enhance antibodydependant cytotoxicity, complement dependant cytotoxicity and serum half-life, humanised antibodies ING-1 (de Bono et al, 2004), 3622W94 (Abdullah et al, 1999;Martin et al, 1999) and fully human IgG1 antibody MT201 (adecatumumab) (Naundorf et al, 2002;Brischwein et al, 2005) were developed. All showed much higher in vitro cytotoxic activity than edrecolomab, but the two high-affinity antibodies ING-1 and 3622W94 turned out to be much less tolerable than edrecolomab due to induction of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cell adhesion molecule was also selected as target for bi-and trispecific antibody therapies. Three T-cell activating, single-chain bispecific antibodies were shown to potently eradicate established and disseminated tumours in immunodeficient and -competent mouse models (Peters et al, 2004;Brischwein et al, 2005;Schlereth et al, 2005a, b), and a related bispecific antibody called E3Bi demonstrated high in-vitro cytotoxicity (Ren-Heidenreich et al, 2004). The trifunctional antibody catumaxomab (anti-Ep-CAM Â anti-CD3) has been safely administered in a phase I/II study to patients suffering from malignant ascites (Stroehlein et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this biological shell game, antibodies evade degradation by serum and lysosomal proteases [5,6]. A region found within Fc is also necessary to induce activation immunotherapeutic mechanisms, such as antibody-dependent cellular cytotoxicity (ADCC) [7,8] or complement-dependent cytotoxicity (CDC) [9,10]. Specifically, Fc γ-receptors on the surface of immune effector cells, such as natural killer cells and macrophages, recognize Fc in antibodies that are bound to disease-relevant receptors on the surface of targeted cells (via interactions involving CDRs within the Fab fragment).…”
Section: Antibody Immunotherapeuticsmentioning
confidence: 99%